Guts : - Lutz, Robert A. (Wiley, 2003)
What do you do with a book that’s filled with controversial, counterintuitive, and downright contrarian statements that stand conventional wisdom on its ear and claim, lightheartedly, to be immutable "laws of business?" If the author is Robert Lutz, you read the book very carefully, probably several times, learn all of the "laws" by heart, and follow them to the letter every chance you get. You also find yourself laughing out loud, shaking your head in wonder, and nodding in agreement. Concluding that his laws have served him well and are generally reliable in any business situation and any industry, he goes on to explain why: * The customer isn’t always right ; * The primary purpose of business isn’t "to make money" ; * When everybody else is doing it, don’t ; * Too much quality can ruin you ; * Financial controls are bad * Disruptive people are an asset * Teamwork isn’t always good